2012
DOI: 10.1111/j.1476-5829.2012.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumour‐associated macrophages in canine mammary tumours

Abstract: Tumour-associated macrophages (TAMs) have already been associated in human breast cancer to a poor prognosis. As a part of a tumoural microenvironment, TAMs have an important contribution influencing neoplastic progression. Hitherto, in canine mammary tumours (CMT) the prognostic value of TAMs has not been reported. In this study, MAC387 immunohistochemical expression was evaluated in 59 CMTs (20 benign and 39 malignant). The TAM value was significantly higher in malignant than benign CMT (P = 0.011). In malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 51 publications
8
30
1
3
Order By: Relevance
“…Tumour‐associated macrophages frequently present characteristics of M2‐phenotype macrophages which are associated with neoangiogenesis, tumour proliferation and consequently a worse prognosis in several different neoplasias . In canine cancers, increased macrophage infiltration has already been proven to have a negative prognostic value in canine mammary tumours . Our study also found an association between macrophage infiltration and markers of tumour proliferation and higher histological grade, but no association was found with angiogenesis.…”
Section: Discussionsupporting
confidence: 60%
“…Tumour‐associated macrophages frequently present characteristics of M2‐phenotype macrophages which are associated with neoangiogenesis, tumour proliferation and consequently a worse prognosis in several different neoplasias . In canine cancers, increased macrophage infiltration has already been proven to have a negative prognostic value in canine mammary tumours . Our study also found an association between macrophage infiltration and markers of tumour proliferation and higher histological grade, but no association was found with angiogenesis.…”
Section: Discussionsupporting
confidence: 60%
“…A positive correlation between microvessel density and mast cells in malignant canine mammary cancer was found, which, in turn, suggests that these immune cells play an important role in canine mammary cancer angiogenesis, similar to human breast cancer [53]. TAMs in canine mammary cancer have already been associated, by our group, with skin ulceration, histological type, nuclear grade, tubular differentiation, and decrease in overall survival [56]. Similarly to human breast cancer, in canine mammary cancer the macrophages also polarize toward the M2 phenotype [57].…”
Section: Inflammatory Cells and Sustained Angiogenesismentioning
confidence: 83%
“…TAMs have also been implicated in promoting tumor invasion and angiogenesis as well as having immunosuppressive effects on the anti-tumor response of lymphocytes by producing various cytokines and chemokines (Nielsen and Schmid, 2017). TAM infiltration has also been associated with vascular endothelial growth factor expression and linked to poor prognosis in canine breast carcinoma (Raposo et al, 2014;Raposo et al, 2015). It is suggested that the peripheral monocyte level correlates with TAM density of the tumor microenvironment (Shibutani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%